2015
DOI: 10.1016/j.chom.2015.05.006
|View full text |Cite|
|
Sign up to set email alerts
|

The PAMP c-di-AMP Is Essential for Listeria monocytogenes Growth in Rich but Not Minimal Media due to a Toxic Increase in (p)ppGpp

Abstract: SUMMARY Cyclic di-adenosine monophosphate (c-di-AMP) is a widely distributed second messenger that appears to be essential in multiple bacterial species, including the Gram-positive facultative intracellular pathogen Listeria monocytogenes. In this study, the only L. monocytogenes diadenylate cyclase gene, dacA, was deleted using a Cre-lox system activated during infection of cultured macrophages. All ΔdacA strains recovered from infected cells harbored one or more suppressor mutations that allowed growth in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
160
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(168 citation statements)
references
References 61 publications
(107 reference statements)
6
160
1
1
Order By: Relevance
“…Interestingly, the growth defects associated with depletion of CdaA can be detected already after approximately three generations in culture medium without IPTG. This is in contrast to what we routinely observe with other strains allowing depletion of essential genes (such as secA), which usually need up to six generations to cause retardation of growth (39) and confirms that cdaA is an essential gene in L. monocytogenes during growth in rich medium (11,12). To conclude, inactivation of cdaR and cdaA has additive negative effects on L. monocytogenes growth.…”
Section: Cdar Does Not Affect Synthesis and Membrane Localization Ofcontrasting
confidence: 50%
See 2 more Smart Citations
“…Interestingly, the growth defects associated with depletion of CdaA can be detected already after approximately three generations in culture medium without IPTG. This is in contrast to what we routinely observe with other strains allowing depletion of essential genes (such as secA), which usually need up to six generations to cause retardation of growth (39) and confirms that cdaA is an essential gene in L. monocytogenes during growth in rich medium (11,12). To conclude, inactivation of cdaR and cdaA has additive negative effects on L. monocytogenes growth.…”
Section: Cdar Does Not Affect Synthesis and Membrane Localization Ofcontrasting
confidence: 50%
“…That processes other than peptidoglycan biosynthesis are affected by depletion of CdaA is in good agreement with our observation that penicillin had no effect on autolysis of CdaA-depleted cells. A recent study revealed that c-di-AMP is essential only for the growth of L. monocytogenes on rich medium (12). It has been shown that the lack of c-di-AMP led to a decrease in intracellular GTP levels and consequently to the activation of several genes that are usually repressed by the pleiotropic transcription factor CodY (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is underlined by the isolation of suppressor mutants of L. monocytogenes that are able to grow in the absence of c-di-AMP. The common theme of those mutants is a global regulatory defect in the CodY regulon that encompasses genes subject to nutritional signaling (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study using L. monocytogenes identified conditions that allow growth of this bacterium in the absence of c-di-AMP: c-di-AMP production was dispensable if the bacterium grew in minimal medium or if the stringent response was inactivated due to a loss of ppGpp synthesis. This suggests that c-di-AMP is required for L. monocytogenes to cope with the potential toxicity of ppGpp (25).…”
mentioning
confidence: 99%